Mengembangkan Industri Keuangan NonBank (IKNB) Syariah: Manakah Prioritas Utama? - Aam Slamet Rusydiana; Abrista Devi (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2018)
The objective of this paper was to formulate model and identify the most priorities criteria to enhance the role of Non Bank-Islamic Financial Industry (Non Bank Financial Services). This research also tried to find which NB-IFI with the highest priorities to be improved. This research also tried to compare the priorities result based on two approaches-methods, there are AHP (Analytic Hierarchy Process) where the network connection is hierarchy, and ANP (Analytic Network Process) where the network connection is feedback. Indepth interview to some academician, practitioners, and regulators who has better knowledge related to Non Bank-Islamic Financial Industry was used to formulate AHP and ANP model. The result of this study indicates that the most priorities criterian to enhance the role of Non Bank-Islamic Financial Industry is tough, manageable, and steady NB-IFI. The most priorities of sub criteria ‘tough, manageable, and steady NB-IFI’ are strengthening the institutional system, modal aspect, and operational activity aspect and business capacity. The most priorities of sub criteria ‘NB-IFI and financial inculsion’ are NB-IFI products development based on the needs of society. The most priorities of sub criteria ‘Human Resource, Infrastructures and Information Technology support’ are NB-IFI infrastructure development to bolster up business process. Alternative priority to enhance NB-IFI in Indonesia is Islamic Financing Institutions. We can conclude that there is no difference results between both approaches were used. Both AHP and ANP have the same priority result to synthesize the most priorities criterian and alternative in this research model.